IDENTIFIKASI SIKAP UNCONDITIONAL POSITIVE REGARD KONSELOR DALAM CERITA RAKYAT KE’ LESAP - Yunus, Fahmi (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2024)
This research will describe the story of Ke' Lesap, the Hero of Madura Island's Independence. From this story, we will analyze and explain in detail the personal portrait of Ke' Lesap, the Hero of Madura Island Independence, as well as the representation of the attitude of unconditional positive regard in the Madurese folklore Ke' Lesap for the development of the moderate personality of the counselor. The Ke' Lesap folklore is the story of a young warrior from Madura who fought for the Madurese people from misery and poverty. The glory of a Ke' Lesap who helps others unconditionally, especially those who are helped are Madurese people from ordinary circles. This attitude is a reflection of the unconditional positive regard attitude.  The research method used is a qualitative descriptive method with the type/design of this research using library research/literature study, namely research whose area of study is libraries or literature. The data collection techniques used in this research are listening, reading, listening and note-taking techniques, as this type of research is literature/library study which is a data collection technique using written sources or reading books. The results of the research show that there are ten types of Ke' Lesap personality which are characteristics of an unconditional positive regard attitude, namely friendly and open, sincere, sympathetic, respectful of others, helpful, firm in reminding, respecting diversity, brave, having a high sense of brotherhood. , and never give up.